Urban mosquito species (Diptera: Culicidae) of dengue endemic communities in the Greater Puntarenas area, Costa Rica - Calderón-Arguedas, Olger (2009)
Field studies were conducted to determine the mosquito species richness in the urban area of Greater Puntarenas in Costa Rica. Two cross-sectional entomological surveys were performed in seven localities of Puntarenas: one survey was performed during the wet season and the other during the dry season. The sections evaluated were determined by applying a stratified cluster sampling method using satellite imagery, and a sample of 26 cells (100x100m) was selected for the study. The number of cells per locality was proportional to the area of each locality. The presence of mosquito larvae and pupae in water-filled artificial and natural containers was determined in each cell. Infestation was expressed as a diversity index per type of container (Ii). Eight types of larvae were identified (Aedes aegypti, Culex quinquefasciatus, Culex interrogator, Culex nigripalpus, Culex corniger, Culex tarsalis, Limatus durhamii and Toxorhynchites theobaldi) and in two cases it was only possible to identify the genus (Culex sp. and Uranotaenia sp.). A. aegypti was the most common species followed by C. quinquefascitus. Diversity of wet environments can explain the co-occurrence of various culicid species in some localities. Although A. aegypti is the only documented disease vector in the area, C quinquefasciatus, C. nigripalpus, and the other species of Culex could be considered potential vectors of other pathogens. The presence and ecology of all mosquito species should be studied to optimize surveillance and prevention of dengue and to prevent the emergence of other mosquito-transmitted diseases.